THE SCIENTIFIC AND PHILOSOPHICAL LEGACY OF THE GREAT EASTERN THINKER NASIR AL-DIN AL-TUSI - Abdullayeva, Firuza (Центр Научных Публикаций (buxdu.uz), 2022)
This article is dedicated to the socio-philosophical opposition of the great scientist Nasiriddin Tusi, who lived and worked in the 13th century. The article also provides a scientific analysis of the scientist's scientific heritage and its role in the development of world science.